Plant aboveground biomass by functional group for alpine tundra and mountain birch woodlands in northern Finland, 2022. - Logan T. Berner; Kathleen M. Orndahl; Patrick Burns (Arctic Data Center, 2023)
This dataset incudes measurements of plant aboveground biomass for 20 sample sites in alpine tundra and mountain birch woodlands across Lapland in northern Finland. The sample sites were measured during August 2022 and spanned a wide range of upland landscapes across the region. Live tree, shrub, graminoid, forb, lichen, and moss aboveground biomass were measured on five plots at each sample site. Moss and lichen biomass were clipped from 0.2 meter (m) x 0.2 m quadrats, while dwarf shrub (less than 30 centimeter (cm) tall), graminoid, and forb biomass were clipped from 0.5 x 0.5 m quadrats, with samples then oven-dried and weighed. Low to tall shrub and tree biomass were estimated by inventorying live stems typically 4 m x 4 m and 8 m x 8 m subplots, respectively, and then applying allometric models that related stem diameter to dry weight. New allometric models were developed for dwarf birch (Betula nana), willow (Salix spp.), and common juniper (Juniperus communis) by harvesting individual plants, measuring stem diameter and oven-dry weight, and fitting non-linear regression models. This dataset includes (1) site metadata; (2) plant functional type biomass for each plot; (3) raw harvest data; (4) raw inventory data; (5) raw shrub allometry data; and (6) shrub allometry regression coefficients. These data were collected as part of a research project focused on mapping plant aboveground biomass across the Arctic tundra biome.